Intra-abdominal metastasis after pelvic primary Synovial Sarcoma resection: case report - Hajri, Amal; Jamaleddine, Khalid; El Wassi, Anas; Erguibi, Driss; Boufettal, Rachid; Jai Rifki, Saad; Chehab, Farid (European Scientific Journal, ESJ, 2024)
Introduction: Synovial sarcoma is a malignant soft tissue sarcoma. It occurs predominantly in young adults. 90% of synovial sarcomas occur in the extremities, they have been reported in other sites, including abdomen and pelvis. Up to 40% of all patients with soft tissue sarcomas develop distant metastasis, despite adequate local disease control. Aim of the article: To provide an update on one of the rarest and most aggressive tumors, to affirm the importance of early management and especially surveillance, and to encourage the codification and the management of these tumors. Presentation of cases: Here, we discuss a case of a 78-year-old female patient, operated 10 years earlier for a pelvic Synovial sarcoma, who presented with intra-abdominal mass to our hospital that eventually turned out to be a metastatic intra-abdominal synovial sarcoma following biopsy. Conclusion: It is important to be aware that primary intraabdominal tumors can occur and delayed metastasis is more typical of synovial sarcoma than of many other sarcomas and should be considered in determining the appropriate frequency and duration of follow-up imaging.